Mobile application for Halal food ingredients identification using optical character recognition - Kartiwi, Mira; Gunawan, Teddy Surya; Anwar, Aqmarina; Fathurohmah, Siti Sarah (Institute of Electrical and Electronics Engineers Inc., 2019)
With the advances in technology and food distribution, today, more and more Muslims are exposed to various manufactured foods imported from non-Muslim countries. Similar exposure also experienced by a Muslim when traveling to a country where Muslims community is a minority. The common challenge in such situation is to identify the food that is halal (permissible or lawful) to be consumed. As a Muslim, it is compulsory to follow the guidance that Quran dictates, which is all foods are Halal except those that are specifically mentioned as Haram (unlawful or prohibited). Hence, it is the aim of this study to address such issue through the development of mobile application. It allows the user to scan the ingredients list in a product, and identify whether any of the items listed might be unlawful to be consumed using optical character recognition.